ANALYSIS OF PREGNANCY OUTCOMES IN PREGNANT WOMEN WITH PLACENTA PREVIA IN THE PERINATAL CENTER, REPUBLIC OF SAKHA (YAKUTIA) FROM 2013 TO 2019 - Баринов, Сергей Владимирович; Неустроева, Татьяна Николаевна (Mother and Baby in Kuzbass, 2020)
The number of publications devoted to the management of pregnant women and delivery of women with placenta previa is growing every year, since this group of pregnant women is associated with a high risk of adverse outcomes, primarily the development of massive bleeding and hysterectomies. The use of organ-preserving methods when performing a cesarean section in pregnant women with placenta previa allows preserving the reproductive organ and avoiding massive blood loss. Aim – to study the outcome of childbirth, the volume of blood loss, surgical interventions in pregnant women with placenta previa. Materials and methods. The data of somatic history, features of the course of pregnancy, childbirth in women with presentation of infectious risk (n = 385) were evaluated. Analyzed: the frequency of hysterectomies, the volume of blood loss during abdominal delivery in women with placenta previa. Results. During the study period, 385 pregnant women with placenta previa were delivered in the Russian Orthodox Church, the frequency of which increased in the Republic of Sakha (Yakutia) from 0.44 % to 0.69 %. The frequency of increments of the placenta was 30.3 %. Of the observed caesarean sections, a history of 44.7 % of women. According to the number of cesarean sections in the anamnesis, the patients were distributed as follows: 23.4 % of pregnant women had a second cesarean section, the third – 18.5 %, and 2.9 % observed a fourth abdominal delivery. Massive intraoperative bleeding was noted in 20.7 % of patients. The frequency of hysterectomies was 23.6 %. Conclusion. Pregnant women with placenta previa are at high risk for the development of massive obstetric bleeding, therefore, to reduce the amount of blood loss, the frequency of hysterectomies, the use of modern methods of stopping bleeding is required.